Optical laminate and image display device using the same

By designing the phase differential layer of the liquid crystal orientation curing layer and thin layer of adhesive in the optical layer of the image display device, the problem of uneven display is solved, and the display effect is achieved.

CN119376002APending Publication Date: 2025-01-28NITTO DENKO CORP
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202411005688.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-26
Filing Date
2024-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing optical laminated body including a liquid crystal orientation curing layer may have uneven display problems in the image display device, especially in different visual recognition environments, where pink thin lines may be conspicuous.

Method used

A optical layer is designed, which contains polarizers with polarizers and the phase differential layer stacked on the polarizer. The phase differential layer is composed of the first and second LCDs to the curing layer. It is layered by layers of the first and second adhesive. Re (650) relationship. At least one layer of adhesive layer is below 300nm, usually below 200nm or less than 100nm.

Benefits of technology

Through this structure, it can effectively suppress the specific display of specific display in the display device, especially in the direction of the absorption axis of the polarizer, avoid the phenomenon of pink fine lines, thereby improving the uniformity of the display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119376002A_ABST
    Figure CN119376002A_ABST
Patent Text Reader

Abstract

The invention provides an optical laminate and an image display device using the same. The optical laminate includes a liquid crystal alignment cured layer and can suppress specific display unevenness when applied to an image display device. An optical laminate according to an embodiment of the present invention has a polarizing plate including a polarizer, and a phase difference layer laminated on the polarizing plate via a first adhesive layer. The phase difference layer includes, in order from the polarizer side, a first liquid crystal alignment cured layer and a second liquid crystal alignment cured layer laminated on the first liquid crystal alignment cured layer via a second adhesive layer. The retardation layer has a circular polarization function or an elliptical polarization function as a whole, and has the relationship Re (450) < Re (550) < Re (650). The thickness of at least one of the first adhesive layer and the second adhesive layer is 300 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and an image display device using the optical layered body. Background Art

[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices, inorganic EL display devices) have rapidly become popular. In image display devices, an optical laminate containing a phase difference film (for example, an anti-reflection film formed by integrating a polarizer and a phase difference film) is used in most cases. In recent years, as the demand for thinning of image display devices has increased, the demand for thinning of optical laminates has also increased. For the purpose of thinning of optical laminates, the thinning of phase difference layers (phase difference films) that contribute greatly to thickness is being promoted. As a representative example of a thin phase difference film, a film (hereinafter referred to as a liquid crystal film) formed by orienting a liquid crystal compound and fixing its orientation state can be cited. Liquid crystal compounds have a particularly large birefringence (Δn) compared to resins, so the thickness of the liquid crystal film that can be used to obtain the desired in-plane phase difference is particularly small compared to the stretched film of the resin film. However, image display devices using an optical laminate including a liquid crystal film may cause display unevenness (specifically, a phenomenon in which thin lines with a particularly conspicuous pink color are visually recognized in the absorption axis direction of the polarizer) depending on the visual environment.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-222282 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide an optical laminate including a liquid crystal alignment solidified layer and capable of suppressing specific display unevenness when applied to an image display device.

[0008] Means for solving problems

[0009] [1] An optical laminate according to an embodiment of the present invention comprises a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via a first adhesive layer, the phase difference layer comprising, in order from the polarizing plate side, a first liquid crystal orientation solidified layer and a second liquid crystal orientation solidified layer laminated on the first liquid crystal orientation solidified layer via a second adhesive layer, the phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650), and the thickness of at least one of the first adhesive layer and the second adhesive layer is less than 300 nm.

[0010] [2] In the above [1], the thickness of the first adhesive layer and the second adhesive layer are each 200 nm or less.

[0011] [3] In the above [1] or [2], at least one of the first adhesive layer and the second adhesive layer has a thickness of 100 nm or less.

[0012] [4] In the above [3], at least one of the first adhesive layer and the second adhesive layer has a thickness of 50 nm or less.

[0013] [5] In any one of the above [1] to [4], the adhesive layer having a thickness of 300 nm or less is composed of a water-based adhesive.

[0014] [6] According to another aspect of the present invention, there is provided an image display device comprising the optical layered body according to [1] to [5] above.

[0015] Effects of the Invention

[0016] According to the embodiment of the present invention, it is possible to realize an optical laminated body which includes a liquid crystal alignment solidified layer and can suppress specific display unevenness when applied to an image display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic cross-sectional view of an optical layered body according to one embodiment of the present invention.

[0018] Description of Reference Numerals

[0019] 10 Polarizer

[0020] 11 Polarizer

[0021] 12. Protective layer

[0022] 13. Protective layer

[0023] 20 Phase difference layer

[0024] 21 first liquid crystal alignment solidification layer

[0025] 22 second liquid crystal alignment solidification layer

[0026] 31 first adhesive layer

[0027] 32 second adhesive layer

[0028] 100 optical laminates DETAILED DESCRIPTION

[0029] Hereinafter, representative embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0030] (Definition of terms and symbols)

[0031] The definitions of terms and symbols in this specification are as follows.

[0032] (1) Refractive index (nx, ny, nz)

[0033] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.

[0034] (2) In-plane phase difference (Re)

[0035] "Re(λ)" is the in-plane phase difference of the film measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference of the film measured at 23°C using light of wavelength 550nm. Re(λ) can be calculated by the formula: Re = (nx-ny) × d, when the thickness of the film is set to d (nm).

[0036] (3) Retardation in the thickness direction (Rth)

[0037] "Rth(λ)" is the phase difference in the thickness direction of the film measured at 23°C using light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction of the film measured at 23°C using light of wavelength 550nm. Rth(λ) can be calculated by the formula: Rth = (nx-nz) × d, when the thickness of the film is set to d (nm).

[0038] (4) Nz coefficient

[0039] The Nz coefficient is calculated by Nz=Rth / Re.

[0040] (5) Angle

[0041] When an angle is mentioned in this specification, unless otherwise specified, the angle includes angles in both clockwise and counterclockwise directions.

[0042] A. Optical laminate

[0043] Figure 1 It is a cross-sectional schematic diagram of an optical laminate of one embodiment of the present invention. The optical laminate 100 shown in the figure has a polarizer 10 and a phase difference layer 20 laminated on the polarizer 10 by means of a first adhesive layer 31. The polarizer 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. Depending on the purpose, at least one of the protective layers 12 and 13 can also be omitted. Therefore, the polarizer can be a so-called double-sided protective polarizer, a so-called single-sided protective polarizer, or can be composed of a polarizer alone. In one embodiment, the polarizer can be a single-sided protective polarizer in which the protective layer 13 is omitted.

[0044] The phase difference layer 20 includes, from the polarizer 10 side, a first liquid crystal orientation solidification layer 21 and a second liquid crystal orientation solidification layer 22 stacked on the first liquid crystal orientation solidification layer 21 by means of a second adhesive layer 32. Therefore, in the phase difference layer 20, the first liquid crystal orientation solidification layer 21 is stacked on the polarizer 10 by means of the first adhesive layer 31. By using a liquid crystal orientation solidification layer as a phase difference layer, the desired in-plane phase difference can be achieved with a thickness that is extremely thin compared to the stretched film of the resin film. As a result, a significant thinning of the optical laminate can be achieved. The phase difference layer 20 as a whole (as a laminate of the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). In one embodiment, the phase difference layer as a whole has an Nz coefficient of, for example, 0.30 to 0.70. It should be noted that in this specification, the "liquid crystal alignment solidified layer" refers to a layer in which liquid crystal compounds are aligned in a predetermined direction and the alignment state is fixed. The "liquid crystal alignment solidified layer" is a concept including an alignment solidified layer obtained by curing liquid crystal monomers.

[0045] In the embodiment of the present invention, the thickness of at least one of the first adhesive layer 31 and the second adhesive layer 32 is 300 nm or less. That is, in the embodiment of the present invention, the thickness of the first adhesive layer 31 may be 300 nm or less, the thickness of the second adhesive layer 32 may be 300 nm or less, or the thickness of each of the first adhesive layer 31 and the second adhesive layer 32 may be 300 nm or less. In addition, when the thickness of either the first adhesive layer 31 or the second adhesive layer 32 is 300 nm or less, the thickness of the other may be greater than 300 nm. The thickness of the first adhesive layer 31 and the second adhesive layer 32 may be, for example, 250 nm or less, 200 nm or less, 180 nm or less, 150 nm or less, 100 nm or less, 70 nm or less, or 50 nm or less, respectively. The thickness of the first adhesive layer 31 and the second adhesive layer 32 may be, for example, 10 nm or more, or 20 nm or more, respectively, independently of each other. It should be noted that the upper limit of the thickness of the adhesive layer having a thickness greater than 300 nm may be, for example, 2000 nm, 1000 nm, 800 nm, or 500 nm.

[0046] The present inventors, while studying the further thinning of an optical laminate comprising a liquid crystal orientation solidification layer as a phase difference layer, discovered the following new topic: an image display device using an optical laminate comprising a liquid crystal orientation solidification layer as a phase difference layer sometimes produces specific display unevenness depending on the visual recognition environment. Specifically, it was found that in the reflection under a 3-wavelength light source, a phenomenon (sometimes referred to as linear unevenness) in which a particularly conspicuous thin line of pink may be visually recognized as a whole in the absorption axis direction of the polarizer may occur. Furthermore, the present inventors conducted an in-depth study on the suppression of such linear unevenness, and found that by suppressing the interference of the optical laminate, the linear unevenness can be suppressed. In addition, the present inventors found that by making the thickness of at least one of the adhesive layer stacked with the polarizer and the phase difference layer, and the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer constituting the phase difference layer stacked, be less than 300nm, so that the interference of the optical laminate can be suppressed, and the linear unevenness can be well suppressed, thereby completing the present invention. In addition, the inventors have found that by setting the thickness of at least one of the layers to about 200 μm or less, linear unevenness can be significantly suppressed, and by setting the thickness of at least one of the layers to about 100 μm or less, linear unevenness can be particularly significantly suppressed. That is, such an effect of the embodiment of the present invention solves a newly discovered problem when studying the further thinning of an optical laminate containing a liquid crystal orientation solidification layer as a phase difference layer, and is an unexpected excellent effect. It should be noted that it is self-evident that the embodiment of the present invention can suppress the display unevenness previously recognized.

[0047] The adhesive layer with a thickness of 300 nm or less in the first adhesive layer 31 and the second adhesive layer 32 is typically made of a water-based adhesive. The adhesive layer with a thickness exceeding 300 nm may be made of a water-based adhesive or other adhesives (eg, an active energy ray-curable adhesive).

[0048] In the optical laminate, the total thickness from the first liquid crystal orientation solidification layer to the second liquid crystal orientation solidification layer is preferably 20 μm or less, more preferably 3 μm to 10 μm. According to an embodiment of the present invention, the problem of newly discovered linear unevenness in an optical laminate comprising a very thin liquid crystal orientation solidification layer can be solved. It should be noted that if the total thickness from the first liquid crystal orientation solidification layer to the second liquid crystal orientation solidification layer is in the above-mentioned range, the total thickness from the polarizer to the second liquid crystal orientation solidification layer (excluding the actual total thickness of the optical laminate including the thickness of the adhesive for bonding to the image display panel) can be, for example, 100 μm or less, and for example, 30 μm to 80 μm.

[0049] From a practical point of view, the optical laminate has an adhesive layer (not shown) as the outermost layer on the second liquid crystal orientation solidified layer side (image display panel side), which can be attached to the image display panel. At this time, it is preferred that a release liner is temporarily bonded to the surface of the adhesive layer until the optical laminate is used. By temporarily attaching the release liner, a roll of the optical laminate can be formed while protecting the adhesive layer.

[0050] Hereinafter, the components of the optical layered body will be described in detail.

[0051] B. Polarizer

[0052] B-1. Polarizer

[0053] The polarizer 11 is typically formed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance (eg, iodine). Examples of the PVA resin include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.

[0054] The PVA resin preferably includes an acetoacetyl-modified PVA resin. If such a structure is used, a polarizer having a desired mechanical strength can be obtained. When the PVA resin as a whole is set to 100 wt %, the blending amount of the acetoacetyl-modified PVA resin is preferably 5 wt % to 20 wt %, more preferably 8 wt % to 12 wt %. If the blending amount is such a range, a polarizer having a more excellent mechanical strength can be obtained.

[0055] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of PVA-based resin. The halide can be compounded in a coating liquid that forms a PVA-based resin layer as a precursor of the polarizer in the manufacturing method described later, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be improved, and therefore, a polarizer with excellent optical properties (representatively, a combination of high polarization degree and high monomer transmittance) can be achieved.

[0056] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.0% to 46.0%, more preferably 42.0% to 45.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more. According to an embodiment of the present invention, even if the single transmittance is in the range as described above, the polarization degree can be maintained in such a range.

[0057] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. By combining such a thin polarizer with a liquid crystal orientation solidification layer, a significant thinning of the optical laminate can be achieved. In addition, if the thickness of the polarizer is in the above range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0058] The polarizer can be produced by any appropriate method. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0059] Specific examples of polarizers composed of a single-layer resin film include polarizers obtained by dyeing and stretching hydrophilic polymer films such as PVA films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers using dichroic substances such as iodine and dichroic dyes, and polyene-based oriented films such as dehydrated PVA and dehydrochlorinated polyvinyl chloride. From the perspective of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.

[0060] The dyeing using iodine is carried out, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching can be carried out after the dyeing treatment or while dyeing. In addition, dyeing can also be carried out after stretching. As required, the PVA film can be subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water and washing it with water before dyeing, not only can the dirt and anti-blocking agent on the surface of the PVA film be cleaned, but also the PVA film can be swollen to prevent uneven dyeing.

[0061] As a specific example of a polarizer obtained using a laminate, there can be cited a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution and stretching it. Furthermore, the stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in a boric acid aqueous solution as needed. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate is shrunk by more than 2% in the width direction by heating while being transported in the length direction. Typically, the manufacturing method of the present embodiment includes sequentially performing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, the crystallinity of the PVA can be improved even when the PVA is coated on the thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA in advance, when immersed in water in the subsequent dyeing process and the stretching process, problems such as the reduction and dissolution of the orientation of the PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and an underwater stretching treatment can be improved. Furthermore, by shrinking the laminate in the width direction using a drying shrinkage treatment, the optical properties can be improved. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or can be used by laminating any appropriate protective layer according to the purpose on the peeling surface of the resin substrate peeled off from the laminate of resin substrate / polarizer, or on the surface on the opposite side of the peeling surface. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Unexamined Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The overall records of these publications are cited in this specification as a reference.

[0062] B-2. Protective layer

[0063] The protective layers 12 and 13 are composed of any appropriate resin film. As the material constituting the resin film, representative examples include cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as polynorbornene, (meth) acrylic resins, polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, and polycarbonate resins. As a representative example of (meth) acrylic resins, (meth) acrylic resins with a lactone ring structure can be listed. (Meth) acrylic resins with a lactone ring structure are, for example, recorded in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, and Japanese Patent Publication No. 2005-146084. These publications are cited in this specification as reference. From the viewpoint of ease of processing into a special shape, cellulose resins are preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low water vapor permeability and excellent durability, cycloolefin resins and (meth)acrylic resins are preferred.

[0064] The optical stack is typically configured on the visual recognition side of the image display device, and the protective layer 12 is typically configured on the visual recognition side. Therefore, the protective layer 12 can be surface treated as needed. As a surface treatment, for example, hard coating, anti-reflection treatment, anti-adhesion treatment, and anti-glare treatment can be listed. And / or, the protective layer 12 can also be implemented as needed to improve the processing of visual recognition when visually recognized across polarized sunglasses (representatively, giving (elliptical) circular polarization function, giving ultra-high phase difference). By implementing such a treatment, even in the case of visually recognizing the display screen across polarized lenses such as polarized sunglasses, excellent visual recognition can be achieved. Therefore, the optical stack can also be suitably applied to image display devices that can be used outdoors.

[0065] In one embodiment, the protective layer 13 is preferably optically isotropic. In this specification, the term "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the thickness direction retardation Rth(550) is -10 nm to +10 nm.

[0066] The thickness of each of the protective layers 12 and 13 is preferably 10 to 80 μm, more preferably 12 to 40 μm, and further preferably 15 to 35 μm. When the protective layer 12 is surface treated, the thickness of the protective layer 12 includes the thickness of the surface treated layer.

[0067] C. Phase difference layer

[0068] As described above, the phase difference layer 20 includes the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22 in order from the polarizing plate side. Furthermore, as described above, the phase difference layer 20 as a whole (as a laminate of the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). Regarding the description of the phase difference layer in this item, when it is simply referred to as a "phase difference layer", it means that it is described as a whole phase difference layer, and when it is simply referred to as a "liquid crystal orientation solidification layer", it means that the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer are collectively described.

[0069] The Re(550) of the phase difference layer 20 is preferably 100 nm to 200 nm, more preferably 110 nm to 180 nm, further preferably 120 nm to 170 nm, and particularly preferably 130 nm to 150 nm. When the Re(550) of the phase difference layer is within such a range, the phase difference layer can be combined with a polarizer to exhibit a good circular polarization function or an elliptical polarization function.

[0070] The phase difference layer 20 has a relationship of Re(450)<Re(550)<Re(650). That is, the phase difference layer 20 preferably shows a wavelength dependence of reverse dispersion in which the phase difference value increases with the wavelength of the measured light. If it is such a structure, a good anti-reflection function can be achieved in a very wide wavelength range. Re(450) / Re(550) is, for example, greater than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and further preferably 0.8 to 0.9. Re(650) / Re(550) is preferably greater than 1.0 and less than 1.15, more preferably 1.03 to 1.1.

[0071] In one embodiment, the Nz coefficient of the phase difference layer 20 can be, for example, 0.30 to 0.70 as described above. Therefore, the phase difference layer 20 shows a refractive index characteristic of nx>nz>ny. According to such a structure, reflection in the oblique direction can be well prevented, and a wide viewing angle of the anti-reflection function can be achieved. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and further preferably 0.45 to 0.55.

[0072] As the liquid crystal compound used in the liquid crystal orientation solidification layer, for example, liquid crystal polymers and liquid crystal monomers can be listed. The liquid crystal compound is preferably capable of polymerization (i.e., liquid crystal monomer). If the liquid crystal compound is capable of polymerization, then by polymerizing after the liquid crystal compound is oriented, the orientation state of the liquid crystal compound can be fixed. Here, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal orientation solidification layer will not undergo a change in temperature, such as that of a liquid crystal compound, resulting in a transition to a liquid crystal phase, a glass phase, or a crystalline phase. As a result, the liquid crystal orientation solidification layer becomes a phase difference layer having excellent stability that is not affected by temperature changes.

[0073] In one embodiment, the liquid crystal orientation solidification layer can be formed using a composition comprising a liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer) that can be polymerized. In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and having liquid crystal properties. The polymerizable group refers to a group participating in the polymerization reaction, preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can participate in the polymerization reaction by an active free radical, acid, etc. produced by a photopolymerization initiator. As a liquid crystal monomer, for example, the polymerizable mesogen compounds described in Japanese Patent Application No. 2002-533742 (WO00 / 37585), EP 358208 (US 5211877), EP 66137 (US 4388453), WO 93 / 22397, EP 0261712, DE 19504224, DE 4408171 and GB 2280445, etc. can be used. Specific examples of such polymerizable mesogen compounds include LC 242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC 3767 (trade name) from Wacker-Chem.

[0074] The liquid crystal compound may be thermotropic or lyotropic in its liquid crystal properties. In addition, the liquid crystal phase may be a nematic liquid crystal or a smectic liquid crystal. From the perspective of ease of manufacture, a nematic liquid crystal having a thermotropic liquid crystal property is preferred.

[0075] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0076] The birefringence Δn of the liquid crystal orientation solidified layer is preferably 0.06 or more, more preferably 0.08 or more, further preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn can be, for example, 0.13, and can be, for example, 0.12. If Δn is in such a range, the desired in-plane phase difference can be achieved with a very thin thickness. As a result, the liquid crystal orientation solidified layer and the optical laminate can be further thinned, which can ultimately contribute to the significant thinning of the image display device.

[0077] The liquid crystal orientation solidified layer can show a reverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measuring light, a positive wavelength dispersion characteristic in which the phase difference value decreases according to the wavelength of the measuring light, or a flat wavelength dispersion characteristic in which the phase difference value hardly changes with the wavelength of the measuring light.

[0078] The first liquid crystal orientation solidification layer 21 can function as a λ / 2 plate, and the second liquid crystal orientation solidification layer 22 can function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal orientation solidification layer is preferably 150nm to 300nm, more preferably 200nm to 270nm, and further preferably 220nm to 260nm; the Re(550) of the second liquid crystal orientation solidification layer is preferably 100nm to 200nm, more preferably 110nm to 160nm, and further preferably 120nm to 140nm. The thickness of the first liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 2 plate. In one embodiment, the thickness of the first liquid crystal orientation solidification layer can be, for example, 2.0μm to 4.0μm. In another embodiment, the thickness of the first liquid crystal orientation solidification layer is preferably 1.7μm or less, more preferably 1.6μm or less, and further preferably 1.5μm or less. In this case, the thickness of the first liquid crystal orientation solidification layer can be, for example, 1.3μm or more. Like this, according to an embodiment of the present invention, the thickness of the first liquid crystal orientation solidification layer can be made thinner than before, and linear unevenness can be suppressed. The thickness of the second liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 4 plate. Specifically, its thickness can be, for example, 0.8μm to 2.5μm. The angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 14° to 16°; the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 74° to 76°. It should be noted that the configuration order of the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer can be opposite, and the angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer and the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer can also be opposite.

[0079] The refractive index of the liquid crystal orientation solidification layer can vary according to the composition forming the liquid crystal orientation solidification layer (substantially the type of liquid crystal compound, the type, quantity, combination, blending amount, etc. of additives). The refractive index of the first liquid crystal orientation solidification layer and the refractive index of the second liquid crystal orientation solidification layer can be the same or different from each other (the refractive index of the first liquid crystal orientation solidification layer can be greater, or the refractive index of the second liquid crystal orientation solidification layer can be greater). The refractive index of the first liquid crystal orientation solidification layer is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. The refractive index of the second liquid crystal orientation solidification layer is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. The refractive index of the first liquid crystal orientation solidification layer and the refractive index of the second liquid crystal orientation solidification layer can also be opposite. The absolute value of the difference between the refractive index of the first liquid crystal orientation solidification layer and the refractive index of the second liquid crystal orientation solidification layer can be, for example, 0.00 to 0.20. The refractive index of the liquid crystal orientation solidification layer is representatively based on the composition of the liquid crystal orientation solidification layer formed in order to obtain the desired optical properties. As a result, linear unevenness sometimes occurs. In this case, according to an embodiment of the present invention, the linear unevenness can be suppressed by making the thickness of at least one of the adhesive layer for stacking the polarizer and the phase difference layer, and the adhesive layer for stacking the first liquid crystal orientation solidified layer and the second liquid crystal orientation solidified layer constituting the phase difference layer less than a specified value.

[0080] It is also possible to introduce a side chain type thermotropic liquid crystal polymer into the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer (essentially the liquid crystal composition forming them). By introducing a side chain type thermotropic liquid crystal polymer, the effect of vertically oriented liquid crystal monomers (homeotropic orientation) can be produced. As a result, the nz of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be increased, and as a result, the Nz coefficient of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be within the above-mentioned desired range. Finally, the Nz coefficient of the phase difference layer can be within the above-mentioned desired range without setting the positive C plate described later.

[0081] As the side chain type thermotropic liquid crystal polymer, a copolymer having a monomer unit containing a thermotropic liquid crystal segment side chain and a monomer unit containing a non-liquid crystal segment side chain is typically used. When the polymer has a thermotropic liquid crystal segment in the side chain, the side chain type liquid crystal polymer can be oriented when the liquid crystal composition is heated to a predetermined temperature. In addition, when the side chain type polymer has a non-liquid crystal segment in the side chain, the non-liquid crystal segment interacts with the photopolymerizable liquid crystal monomer, which can produce an effect of vertically aligning the photopolymerizable liquid crystal monomer.

[0082] As the side chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used.

[0083]

[0084] In formula (I), R 1 is a hydrogen atom or a methyl group, R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and X 1 is -CO2- or -OCO-. a is an integer of 1 to 6, and b and c are 1 or 2 each independently.

[0085] In formula (II), R 3 is a hydrogen atom or a methyl group, R 4 It is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III).

[0086]

[0087] In formula (III), R 5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.

[0088] The ratio of the liquid crystal monomer unit to the non-liquid crystal monomer unit in the side chain type liquid crystal polymer can be appropriately set according to the purpose. Relative to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit, the ratio (molar ratio) of the non-liquid crystal monomer is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. If it is such a structure, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.

[0089] The ratio of the liquid crystal monomer to the side chain liquid crystal polymer in the liquid crystal composition can be appropriately set according to the purpose. When the content of the side chain liquid crystal polymer is high, there is a tendency for the Nz coefficient to become smaller; when the content of the liquid crystal monomer is high, there is a tendency for the Nz coefficient to become larger. Relative to the content of the side chain liquid crystal polymer, the content of the liquid crystal monomer is preferably 1.2 times to 20 times, more preferably 1.3 times to 10 times, further preferably 1.4 times to 9 times, and particularly preferably 1.5 times to 8 times. If it is such a structure, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.

[0090] Details of the side chain type liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921. The description of this patent is incorporated herein by reference.

[0091] The phase difference layer 20 may further include a positive C plate. The refractive index characteristics of the positive C plate show a relationship of nz>nx=ny. The phase difference Rth(550) in the thickness direction of the positive C plate is preferably -20nm~-300nm, more preferably -30nm~-250nm, further preferably -40nm~-200nm, and particularly preferably -50nm~-150nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the positive C plate can be less than 10nm.

[0092] The positive C plate can be formed, for example, using a composition containing the above-mentioned side chain type liquid crystal polymer. As a specific example of the method for forming the positive C plate, there can be cited the method described in

[0020] to

[0028] of Japanese Patent Publication No. 2002-333642. At this time, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and further preferably 0.5 μm to 5 μm.

[0093] D. First adhesive layer and second adhesive layer

[0094] As described above, the adhesive layer with a thickness of less than 300nm in the first adhesive layer 31 and the second adhesive layer 32 can be typically composed of a water-based adhesive. The adhesive layer with a thickness exceeding 300nm can be composed of any appropriate adhesive (here, for convenience, also including adhesives) as long as the effect of the embodiment of the present invention can be obtained, and such an adhesive layer can also be typically composed of a water-based adhesive. The water-based adhesive is formed by applying an aqueous solution and drying as described later, and therefore shrinks less than a curing adhesive. As a result, the thickness deviation of the adhesive layer becomes smaller, thereby suppressing interference and suppressing linear unevenness. The water-based adhesive is described below. In this item, unless otherwise specified, the first adhesive layer and the second adhesive layer are unified as adhesive layers for description.

[0095] The water-based adhesive typically includes a polyvinyl alcohol (PVA) resin. The adhesive layer can be typically formed by applying a PVA resin aqueous solution and drying it. The average degree of polymerization of the PVA resin contained in the aqueous solution is preferably about 100 to 5000, and more preferably 1000 to 4000. The average degree of saponification is preferably about 85 mol% to 100 mol%, and more preferably 90 mol% to 100 mol%. When the average degree of polymerization and the average degree of saponification are in such a range, an adhesive layer (substantially a first adhesive layer) having excellent adhesion to the polarizer can be formed.

[0096] The PVA resin preferably contains an acetoacetyl group. This is because the adhesion with the polarizer and the protective layer is excellent, and an optical laminate with excellent durability can be obtained. The PVA resin containing an acetoacetyl group can be obtained, for example, by reacting the PVA resin with diketene using any method. The acetoacetyl modification degree of the PVA resin containing an acetoacetyl group is typically 0.1 mol% or more, preferably about 0.1 mol% to 40 mol%, more preferably 1 mol% to 20 mol%, and particularly preferably 2 mol% to 7 mol%. It should be noted that the acetoacetyl modification degree is a value measured by NMR.

[0097] The resin concentration in the PVA-based resin aqueous solution is preferably 0.1 wt% to 15 wt%, more preferably 0.5 wt% to 10 wt%. The viscosity of the aqueous solution is preferably 1 to 50 mPa·s. The pH of the aqueous solution is preferably 2 to 6, more preferably 2.5 to 5, further preferably 3 to 5, and particularly preferably 3.5 to 4.5. When the resin concentration and viscosity of the PVA-based resin aqueous solution are within such a range, an adhesive layer having a desired thickness according to an embodiment of the present invention can be formed.

[0098] In one embodiment, the PVA resin aqueous solution (resulting in the adhesive layer) may contain a metal compound colloid. The metal compound colloid is a substance in which metal compound particles are dispersed in a dispersion medium, and the particles are electrostatically stabilized due to mutual repulsion of like charges, and thus have long-term stability.

[0099] The average particle size of the particles forming the metal compound colloid can be set to any appropriate value as long as it does not adversely affect the optical properties such as transparency and polarization characteristics. It is preferably 1 nm to 100 nm, and more preferably 1 nm to 50 nm. This is because the particles can be uniformly dispersed in the adhesive layer.

[0100] As the metal compound, any appropriate compound can be used. For example, metal oxides such as aluminum oxide, silicon dioxide, zirconium oxide, and titanium oxide; metal salts such as aluminum silicate, calcium carbonate, magnesium silicate, zinc carbonate, barium carbonate, and calcium phosphate; and minerals such as diatomaceous earth, talc, clay, and kaolin. It is preferred to use a metal compound colloid having a positive charge. As the metal compound, aluminum oxide, titanium oxide, and the like can be listed, and aluminum oxide is particularly preferred.

[0101] E. Image display device

[0102] The optical laminate described in the above items A to D can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device using such an optical laminate. As representative examples of image display devices, liquid crystal display devices and organic EL display devices can be listed. The image display device of the embodiment of the present invention is typically equipped with the optical laminate described in the above items A to D on its visual recognition side.

[0103] Example

[0104] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods and evaluation methods in the examples are as follows. Unless otherwise specified, "parts" and "%" in the examples are by weight.

[0105] (1) Thickness

[0106] The measurement was performed using an interferometer film thickness meter (manufactured by Otsuka Electronics Co., Ltd., “MCPD 9800”).

[0107] (2) Linear unevenness

[0108] A conventional acrylic adhesive was placed on the second liquid crystal orientation cured layer side of the optical laminate obtained in the examples and comparative examples, and the optical laminate was bonded to a V3 reflector (manufactured by NEODIS) with the aid of the acrylic adhesive as a test sample. The test samples obtained were visually observed under a 3-wavelength fluorescent lamp and evaluated according to the following criteria.

[0109] 1: No linear unevenness was observed

[0110] 2: Slight linear unevenness is observed

[0111] 3: Linear unevenness was observed, but it was to a practically tolerable level.

[0112] 4: Linear unevenness is observed to a degree that is not acceptable in practical use

[0113] 5: Linear unevenness is obvious.

[0114] [Manufacturing Example 1: Preparation of water-based adhesive]

[0115] A water-based adhesive is obtained by mixing 6.02 parts of acetoacetyl-modified PVA (polymerization degree 1200, acetoacetyl modification degree 4.6%, saponification degree 99.0 mol% or more, solid content concentration 4%, manufactured by Mitsubishi Chemical Corporation, trade name "Gohsenx Z-200"), 25 parts of an aqueous solution containing positively charged alumina colloid (average particle size 15 nm) at a solid content concentration of 3.2%, and 18.98 parts of pure water.

[0116] [Example 1]

[0117] 1. Preparation of polarizer

[0118] 1-1. Preparation of polarizer

[0119] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.

[0120] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating solution).

[0121] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.

[0122] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).

[0123] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0124] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained would be a desired value (dyeing treatment).

[0125] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0126] Then, while the laminate is immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio becomes 5.5 times.

[0127] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0128] Thereafter, the film was dried in an oven maintained at approximately 90° C. while being brought into contact with a SUS heating roll maintained at a surface temperature of approximately 75° C. (drying shrinkage treatment).

[0129] In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, thereby obtaining a polarizing plate having a structure of resin substrate / polarizer. The single-unit transmittance Ts of the polarizer was 43.3%.

[0130] 1-2. Preparation of polarizing film

[0131] The HC-COP film is attached to the surface of the obtained polarizer (the surface on the opposite side to the resin substrate) by means of an ultraviolet curing adhesive. It should be noted that the HC-COP film is a film having an HC layer (thickness 4 μm) formed on a cycloolefin resin (COP) film (thickness 25 μm), and is attached in such a way that the COP film becomes the polarizer side. In addition, the Re (550) of the COP film is 135 nm. Next, the resin substrate is peeled off to obtain a polarizing plate having a structure of HC layer / COP film (protective layer) / polarizer.

[0132] 2. Fabrication of phase difference layer

[0133] A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase ("Paliocolor LC 242" manufactured by BASF, the following chemical formula) was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 30% by weight. A surfactant ("BYK-360" manufactured by BYK-Chemie) and a photopolymerization initiator ("Omnirad 907" manufactured by IGM Resins) were added to the solution to prepare a liquid crystal composition solution. The amount of surfactant and polymerization initiator added was set to 0.01 parts by weight and 3 parts by weight, respectively, relative to 100 parts by weight of the photopolymerizable liquid crystal compound. As a substrate, a biaxially stretched norbornene film ("ZEONOR FILM" manufactured by ZEON Japan, thickness 33μm, Re(550) = 135nm) was prepared. The above-mentioned liquid crystal composition was applied to the substrate using a rod coater in a manner such that Re(550) became 240nm, and the liquid crystal was oriented by heating at 100°C for 3 minutes. After cooling to room temperature, the samples were irradiated in a nitrogen atmosphere with a cumulative light intensity of 400 mJ / cm 2 The substrate was cured by ultraviolet light to obtain a laminate having a structure of a substrate / first liquid crystal orientation solidification layer. The first liquid crystal orientation solidification layer was horizontally oriented (homogeneous orientation) and had a thickness of 1.7 μm. A laminate of a substrate / second liquid crystal orientation solidification layer (horizontally oriented, 0.92 μm thick, Re (550) = 130 nm) was obtained in the same manner as above except that the coating thickness was changed.

[0134]

[0135] 3. Fabrication of optical laminates

[0136] After the first liquid crystal orientation solidification layer is attached to the surface of the polarizer of the polarizer with the help of the adhesive of Manufacturing Example 1 (thickness 50nm after drying), the substrate is peeled off. Next, the second liquid crystal orientation solidification layer is attached to the surface of the first liquid crystal orientation solidification layer with the help of the adhesive of Manufacturing Example 1 (thickness 50nm after drying), and the substrate is peeled off to obtain an optical laminate having a structure of polarizer / first adhesive layer / first liquid crystal orientation solidification layer / second adhesive layer / second liquid crystal orientation solidification layer. In the optical laminate, the angle between the transmission axis of the polarizer of the polarizer and the slow axis of the first liquid crystal orientation solidification layer is 15°, and the angle between the transmission axis of the polarizer of the polarizer and the slow axis of the second liquid crystal orientation solidification layer is 75°. The obtained optical laminate is provided for the above-mentioned "linear unevenness" evaluation. The results are shown in Table 1.

[0137] [Examples 2 to 10 and Comparative Examples 1 to 5]

[0138] The optical laminate was obtained in the same manner as in Example 1 except that the thicknesses of the first adhesive layer and the second adhesive layer were changed as shown in Table 1. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1. It should be noted that the description of "(UV)" in Examples 9 and 10 of Table 1 means that an active energy ray (ultraviolet) curing adhesive was used instead of a water-based adhesive.

[0139] [Table 1]

[0140] First adhesive layer (nm) Second adhesive layer (nm) Linear unevenness Example 1 50 50 1 Example 2 200 200 2 Example 3 1000 50 1 Example 4 1000 100 1 Example 5 1000 200 2 Comparative Example 1 1000 500 4 Comparative Example 2 1000 1000 4 Comparative Example 3 2000 2000 5 Example 6 50 1000 1 Example 7 100 1000 2 Example 8 200 1000 3 Comparative Example 4 500 1000 4 Comparative Example 5 500 500 4 Example 9 50(UV) 50(UV) 2 Example 10 200(UV) 200(UV) 3

[0141] [evaluate]

[0142] As is clear from Table 1, according to the examples of the present invention, linear unevenness can be suppressed. Furthermore, as is clear from the comparison between Examples 4 and 7 and between Examples 5 and 8, by reducing the thickness of the second adhesive layer, the effect of the embodiment of the present invention becomes significant. Furthermore, as is clear from the comparison between Examples 1 and 9 and between Examples 2 and 10, by using a water-based adhesive, the effect of the embodiment of the present invention becomes significant.

[0143] Industrial Applicability

[0144] The optical laminate according to the embodiment of the present invention can be suitably used in image display devices (typically, liquid crystal display devices and organic EL display devices).

Claims

1. An optical laminate comprising a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via a first adhesive layer, The phase difference layer includes, in order from the polarizing plate side, a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer laminated on the first liquid crystal alignment solidified layer via a second adhesive layer. The phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). At least one of the first adhesive layer and the second adhesive layer has a thickness of 300 nm or less.

2. The optical layered body according to claim 1, wherein: The thickness of the first adhesive layer and the second adhesive layer is respectively 200 nm or less.

3. The optical layered body according to claim 1, wherein: At least one of the first adhesive layer and the second adhesive layer has a thickness of 100 nm or less.

4. The optical laminate according to claim 3, wherein: At least one of the first adhesive layer and the second adhesive layer has a thickness of 50 nm or less.

5. The optical layered body according to claim 1, wherein: The adhesive layer having a thickness of 300 nm or less is composed of a water-based adhesive. 6 . An image display device comprising the optical layered body according to claim 1 .

Citation Information

Patent Citations

  • Liq. crystalline (LC) material

    DE19504224A1

  • Novel polymerizable liquid crystalline compounds

    DE4408171A1

  • Liquid crystalline reticulated polysiloxanes

    EP0066137A1

  • Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer

    EP0261712A1

  • Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups

    EP0358208A2